Hospitalized Coronavirus Disease-2019 Patients’ Conversion of Bi-Level Positive Airway Pressure Machines into Ventilators: Emergency Use Procedure - Hugh A. Cassiere; Stanley John; Todd Goldstein (Research and Practice in Anesthesiology, 2024)
During March 2020 New York State was facing a shortage of tens of thousands of ventilators. City and state officials were rapidly trying to source more of the machines, which were required in the sickest patients who were critically-ill with coronavirus disease-2019 (COVID-19). In the community hospitals, there were 792,417 beds, with 3532 emergency departments (EDs) and 96,500 intensive care unit (ICU) beds, of which 23,000 were neonatal and 5100 pediatric, leaving just under 68,400 ICU beds of all types for the adult population.